Maglev Trains Key Underlying Technologies - Liu, Zhigang; Long, Zhiqiang; Li, Xiaolong; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
The motion of the train depends on the traction of linear motors in the vehicle. This book describes a number of essential technologies that can ensure the safe operation of Maglev trains, such as suspension and orientation technologies, network control and diagnosis technologies. This book is intended for researchers, scientists, engineers and graduate students involved in the rail transit industry, train control and diagnosis, and Maglev technology.
Maglev Train Overview -- Technology Development and Application Research of Maglev Control -- Modeling and Controller Design of Suspension System of Maglev Train -- Control and Diagnosis System of Maglev Train -- Maglev Train Control and Diagnosis Networks -- The Position and Speed Detection Technology Based on Loop-cable for Low-speed Maglev Train.
Keywords: Engineering; Energy efficiency; Automotive engineering; Control engineering; Robotics; Mechatronics; Power electronics; Engineering; Control, Robotics, Mechatronics; Automotive Engineering; Power Electronics, Electrical Machines and Networks; Energy Efficiency (incl. Buildings).; Electronic books